Competência motora em crianças: uma discussão sobre a participação da família e das políticas publicas - Nakai, Emiko Harumi Duarte (2021)
The changes in children's lifestyle, especially the involvement with video games, have impacted on the level of motor competence and influenced in the state of health during childhood, adolescence and adulthood. This study aimed to compare motor performance among 10-year-old children who dedicate their free time to play mostly with digital games and those who play outdoors the most. An anamnesis was used to quantify the daily time spent playing outdoors and playing video games. To assess motor competence, the KTK Motor Coordination test - Koperkoordinations Test For Kinder was used. The results show that the group that plays video games presented "very weak" motor performance score for the age of 10, while the group that plays outdoors presented a "good" level of motor performance. The role of public policies that favour equal opportunities for the practice of physical activities and sports were discussed, as well as the role of the family in stimulating and being a model for the involvement in sports and physical activities. It was concluded that the type of activity performed during free time impacts on the level of motor performance.